The governance of Atlantic ports in medieval Castile - Ana María Rivera Medina; Enrique Ruiz Pilares (Mélanges de la Casa de Velázquez)
Spanish historiography has studied widely the political strategies surrounding maritime affairs, producing numerous volumes on coastal or ports realities, both local and regional. This essay offers a comparative vision of the different modes of administration in the Castilian Atlantic’s ports. Firstly, to analyse the system comprising ports in the Iberian north. Secondly, to explicate the established system in the Guadalquivir’s estuary and in the Bay of Cadiz. Although both systems were constructed independently, they converged in maritime traffic while displaying two distinct models of ports administration. The main differences between both models are determined by the degree of intervention of official bodies, local oligarchies, and mercantile institutions.